Comparing the Expressions of Vitamin D Receptor, Cell Proliferation, and Apoptosis in Gastric Mucosa With Gastritis, Intestinal Metaplasia, or Adenocarcinoma Change - Chen, Li-Wei; Chang, Liang-Che; Hua, Chung-Ching; Cheng, Tzu-Chien; Lee, Chin-Chan (Frontiers in Medicine, 2021)
Background: This study aimed to compare the expression of vitamin D receptor (VDR), cell proliferation, and apoptosis in the gastric mucosa of patients with gastritis, intestinal metaplasia (IM), and adenocarcinoma using artificial intelligence. Material and methods: This study retrospectively enrolled patients at the Keelung Chang Gung Memorial Hospital from November of 2016 to June, 2017, who were diagnosed with gastric adenocarcinoma. The inclusion criteria were patients’ pathologic reports that revealed all compartments of Helicobacter pylori infection, gastritis, IM, and adenocarcinoma simultaneously in the same gastric sample. Tissue slides after immunohistochemical (IHC) staining were transformed into digital images using a scanner and counted using computer software (QuPath and ImageJ). IHC staining included PA1-711 antibody for VDR, Ki67 antigen for proliferation, and M30 antibody CK18 for apoptosis. Results: Twenty-nine patients were included in the IHC staining quantitative analysis. The mean age was 69.1 ± 11.3 y/o. Most (25/29, 86.2%) patients had poorly differentiated adenocarcinoma. The mean expression of Ki67 and CK18 increased progressively from gastritis and IM to adenocarcinoma, with statistical significance (P < 0.05). VDR expression did not correlate with Ki67 or CK18 expression. Ki67 expression was positively correlated with CK18 expression in gastric mucosa. Survival time was only correlated with tumor stage (correlation coefficient=-0.423, P value<0.05), but was not correlated with the expression of VDR, Ki67, and CK18. Conclusion: Ki67 expression and CK18 expression progressively increased in the areas of gastritis, IM, and adenocarcinoma. Ki67 expression was positively correlated with CK18 expression in gastric mucosa. No correlation between VDR expression and Ki67 or CK18 expression was found in this study.